2015
DOI: 10.1097/nmd.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

North American Prodrome Longitudinal Study (NAPLS 2)

Abstract: In studies describing the long-term follow-up up of youth at clinical high risk (CHR) of psychosis, little attention has been given to details of specific prodromal symptoms. In this paper we describe the prodromal symptoms of 764 CHR participants recruited in the multi-site North American Prodrome Longitudinal Study (NAPLS). Symptoms were rated on the Scale of Prodromal Symptoms (SOPS) at baseline and 6, 12, 18 and 24 month follow-ups. Clinical outcome at the 2-year assessment was categorized as psychotic, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
180
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 200 publications
(199 citation statements)
references
References 22 publications
12
180
2
2
Order By: Relevance
“…Suspiciousness and unusual thought content are 2 of the most common attenuated psychotic symptoms, 32 suspiciousness was a predictor in RAP and unusual thought content was a predictor in PREDICT. Other prediction models such as the North American Prodromal Study (NAPLS1) reported that both unusual thought content and suspiciousness were significant predictors in their model, 4 and later in NAPLS 2 33 both unusual thought and suspiciousness were highly relevant in prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Suspiciousness and unusual thought content are 2 of the most common attenuated psychotic symptoms, 32 suspiciousness was a predictor in RAP and unusual thought content was a predictor in PREDICT. Other prediction models such as the North American Prodromal Study (NAPLS1) reported that both unusual thought content and suspiciousness were significant predictors in their model, 4 and later in NAPLS 2 33 both unusual thought and suspiciousness were highly relevant in prediction.…”
Section: Discussionmentioning
confidence: 99%
“…HCs were excluded if they had a first-degree relative with a current or past psychotic disorder. We have previously reported a more detailed description of recruitment procedures, ascertainment, and inclusion and exclusion criteria (Addington et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Perceptual abnormalities in CHR differ from full-blown hallucinations by their limited frequency, duration, severity, and the relative intact ability of the individual to question the reality of hallucinatory experience (McGlashan et al, 2010). As in psychotic disorders, perceptual abnormalities are one of the most frequently endorsed attenuated psychotic symptoms in CHR populations (Addington et al, 2015). …”
Section: Introductionmentioning
confidence: 99%